Translating social items from the Tibetan Epic “King Gesar” into english: what a corpus-based analysis reveals and how it can help - Zhou, Yuqiao; Halim, Hazlina Abdul; Ujum, Diana Abu; Wong, Ling Yann (Academy Publication, 2024)
The Ge Sa-er (also known as Gesar) saga has been handed down for above 1000 years by Tibetan Chinese, Mongolian Chinese, the Tu and the Naxi, describing a heroic story in present-day Kangba Tibetan area. This article analyse the English translation of social discourse in the Ge Sa-er version retold by Alai (2009). Due to different knowledge shared by source and target readers, it is difficult to represent the source social meaning in the English translation. Aiming to resolve the translation problems revealed by social cognition, this article uses statistical methods together with corpus to conduct stylistic analyses on Ge Sa-er Wang (Alai, 2009). An unexpected finding of this research is that the data from statistical methods can better predict the translation difficulties of Ge Sa-er Wang than the data from corpus. Based on the stylistic features of Ge Sa-er Wang, we propose a social discourse translation model for Chinese ethnic minority literature.